Mono(alkyne)cobalt complexes and electron-rich alkynes: the formation of an alkyne-bridged dinuclear cobalt complex by a one-pot procedure - Werz, Daniel B.; Gleiter, Rolf; Rominger, Frank (European journal of inorganic chemistry, 2004)
[η2-Bis(tert-butylsulfonyl)acetylene](carbonyl)(η5-trimethylsilylcyclopentadienyl)cobalt (2c) proved to be reactive towards bis(telluro)- and bis(seleno)-substituted alkynes 3 and 4, respectively, to yield push-pull-substituted CpCo-stabilized cyclobutadiene complexes. By utilizing the unsymmetrical diyne 6 and the symmetrical bis(thio)-substituted triyne 7 it was shown that only the most electron-rich triple bond was attacked by the electrophilic compound 2c. In the case of 7 a dinuclear CpCo-stabilized cyclobutadiene complex 14 bridged by one acetylene moiety was obtained. All the reactions could be carried out at room temperature under rather mild conditions. X-ray investigations of 8, 12, 14a, and 15 show almost equal C−C bond lengths in the cyclobutadiene moieties. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)